Maintenance and Repair of BMV Brand Patient Monitor Equipment, Type BMO-200 at STIKES Semarang - Arya Surya Andika; Imam Tri Harsoyo; Mohammad Rofi’i (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to carry out maintenance, and repair, on the BMV BMO 200 Patient Monitor used at STIKES Semarang. This device is vital in monitoring patients' physiological conditions such as heart rate, blood pressure, body temperature, and oxygen saturation. The identified issue was a blurry LCD screen caused by aged backlight components. The study employed a hands-on approach and direct observation. The stages included damage analysis, replacement of the backlight and polarizer components, and calibration using a fluke meter and voltage measurement. The repair results showed that replacing the entire LCD module restored a clear display and returned the device to proper working condition. This research highlights the importance of regular maintenance and calibration in ensuring the reliability of medical equipment for patients.